1992
DOI: 10.1055/s-2007-1021245
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Skating: Physiological Responses and Comparison with Roller Skiing

Abstract: The use of in-line skates has become popular in recent years for recreational and conditioning purposes. This investigation evaluated the physiological responses of ten subjects during in-line skating on a flat track with three different in-line skating techniques. The double pole technique demonstrated the greatest economy with oxygen uptake requirements that were approximately 12% lower (p less than 0.05) than conventional skating (without poles) or the V1 skate technique. Across the investigated velocity sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Skating on 8 wheels is not only healthy [6,9,13,16,17,21] but, as our study clearly showed, dangerous as well. The incidence of injuries is relatively great due to the high speeds of 20-30 km/h, even 50 km/h, and the lack of basic knowledge and techniques.…”
Section: Discussionsupporting
confidence: 48%
“…Skating on 8 wheels is not only healthy [6,9,13,16,17,21] but, as our study clearly showed, dangerous as well. The incidence of injuries is relatively great due to the high speeds of 20-30 km/h, even 50 km/h, and the lack of basic knowledge and techniques.…”
Section: Discussionsupporting
confidence: 48%
“…Despite these discrepancies, the results of both studies support the conclusion that in-line skating at a preferred level of exertion is suitable for improving cardiovascular fitness in healthy, recreationally trained adults. In addition, other in-line skating studies that involved trained athletes from different sports also support this conclusion (Baum et al, 1999;Carroll et al, 1993;Fedel et al, 1995;Hoffman et al, 1992;Martinez et al, 1993;Snyder et al, 1993). Thus, in-line skating could generally be considered as an exercise mode suitable for eliciting favourable cardiovascular training effect in individuals of varying levels of fitness and in-line skating ability.…”
Section: S28mentioning
confidence: 78%
“…To date, several studies have explored the physiological responses to in‐line skating (Baum et al, 1999; de Boer, Vos, Hutter, de Groot, & van Ingen Schenau, 1987; Fedel et al, 1995; Foster et al, 1999; Hoffman, Jones, Bota, Mandli, & Clifford, 1992; Martinez, Ibanez Santos, Grijalba, Santesteban, & Gorostiaga, 1993; Koepp & Janot, 2008; Melanson, Freedson, Webb, Jungbluth, & Kozlowski, 1996; Rundell, 1996; Snyder, O'Hagan, Clifford, Hoffman, & Foster, 1993; Wallick et al, 1995) and compared it with running (Koepp & Janot, 2008; Martinez et al, 1993; Melanson et al, 1996; Rundell, 1996; Snyder et al, 1993), cycling (Foster et al, 1999; Martinez et al, 1993; Snyder et al, 1993), roller skiing (Baum et al, 1999; Hoffman et al, 1992) and ice skating (Carroll, Bacharach, Kelly, Rudrud, & Karns, 1993; de Boer et al, 1987). These studies have generally shown that in‐line skating is an appropriate form of exercise for promoting cardiovascular fitness.…”
Section: Introductionmentioning
confidence: 99%
“…50.5). However, since trained individuals may 648 sport-specific nutrition require high speeds to obtain cardiovascular benefits from in-line skating, skating up hill may be required (Hoffman et al 1992;Snyder et al 1993). 50.6) or in-line skating should also be performed (de Boer et al 1987a(de Boer et al , 1987b(de Boer et al , 1987cde Groot et al 1987;Kandou et al 1987).…”
Section: Training Practicesmentioning
confidence: 99%